1987
DOI: 10.1067/mva.1987.avs0050329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of left atrial to left femoral artery bypass and renin-angiotensin system blockade on renal blood flow and function during and after thoracic aortic occlusion

Abstract: Temporary thoracic aortic occlusion can result in renal insufficiency with or without adjuncts to avoid distal hypoperfusion. In a canine model of thoracic aortic occlusion, left atrial to left femoral bypass was compared with blockade of the renin-angiotensin system. Renin-angiotensin system blockade with the converting enzyme inhibitor, MK422, resulted in restoration of baseline renal blood flow and glomerular filtration 30 minutes after cross-clamp release. Left atrial to left femoral bypass resulted in sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
4

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Previous studies have shown that renin activity is increased following aortic crossclamping, with angiotensin II production potentially compromising renal hemodynamics. 20,21 Conversely, ovine septic shock studies have shown that angiotensin II administration has beneficial effects, with an improvement in creatinine clearance and mitochondrial function despite a decrease in renal blood flow. 12,13 In trauma patients, while serum vasopressin and epinephrine increased, there was no difference in serum angiotensin when compared to non-injured control.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that renin activity is increased following aortic crossclamping, with angiotensin II production potentially compromising renal hemodynamics. 20,21 Conversely, ovine septic shock studies have shown that angiotensin II administration has beneficial effects, with an improvement in creatinine clearance and mitochondrial function despite a decrease in renal blood flow. 12,13 In trauma patients, while serum vasopressin and epinephrine increased, there was no difference in serum angiotensin when compared to non-injured control.…”
Section: Discussionmentioning
confidence: 99%
“…Ο αποκλεισμός της θωρακικής αορτής συνδέεται με σοβαρή (85% -94%) μείωση της νεφρικής αιματικής ροής, του ποσοστού παρεγχυματικής διήθησης και της διούρησης. (104,130,(346)(347)(348) Σε ένα πειραματικό μοντέλο με αποκλεισμό της νεφρικής αρτηρίας, η νεφρική αιματική ροή επέστρεψε αμέσως στις πρότερες τιμές, κατόπιν απελευθέρωσης της νεφρικής αρτηρίας, (349,350) ενώ η απελευθέρωση της θωρακικής αορτής συνδέθηκε με παρατεταμένη μετισχαιμική μείωση και της νεφρικής αιματικής ροής και του ποσοστού παρεγχυματικής διήθησης. (104,130,346,348) Οι λόγοι αυτής της διαφοράς μπορεί να οφείλονται στις ειδικές νευροορμονικές διαταραχές (συμπεριλαμβάνοντας την ενεργοποίηση των ουδετεροφίλων και την απελευθέρωση διαβιβαστών) που ακολουθούν τον αορτικό αποκλεισμό, αλλά εμφανώς δεν συμβαίνουν, ύστερα από αποκλεισμό της νεφρικής αρτηρίας.…”
Section: β νεφροίunclassified
“…Η προαντιμετώπιση με αναστολείς του μετατρεπτικού ενζύμου, συνδέθηκε με πλήρη επιστροφή της νεφρικής αρτηριακής ροής και της παρεγχυματικής διήθησης στα φυσιολογικά, ενώ σε ζώα ελέγχου, η νεφρική αιματική ροή επέστρεψε μόνο γύρω στο 50% στις πρότερες τιμές. (136,348) Οι τιμές της νεφρικής αιματικής ροής σε ζώα που προαντιμετωπίσθηκαν με αναστολείς του μετατρεπτικού ενζύμου, ήταν χαμηλότερες κατά τη διάρκεια του αορτικού αποκλεισμού και υψηλότερες αμέσως μετά την απελευθέρωση σε σύγκριση με τις παρατηρήσεις ελέγχου. (348) Με άλλα λόγια, το προστατευτικό αποτέλεσμα των αναστολέων του μετατρεπτικού ενζύμου, δεν είναι κατά τη διάρκεια, αλλά μάλλον μετά τον αορτικό αποκλεισμό.…”
Section: β νεφροίunclassified
See 2 more Smart Citations